The composition of cosmic rays according to the data on EAS cores - S. B. Shaulov, V. A. Ryabov, S. E. Pyatovsky, A. L. Shepetov, V. V. Zhukov (SciPost Physics Proceedings, 2023)
The main purpose of this work is to find the causes of the break of the cosmic ray spectrum at an energy of 3 PeV, which is called the knee. The solution of the problem is associated with the determination of the nuclear composition of cosmic rays in the knee area. The conclusions of this work are based on the analysis of the characteristics of the EAS cores obtained using X-ray emulsion chambers. According to these data, a number of anomalous effects are observed in the knee region, such as scaling violation in the spectra of secondary hadrons, an excess of muons in EAS with gamma families and others. At the same energies equivalent to 1-100 PeV the laboratory system colliders show scaling behavior. So analysis of the data on the EAS cores suggests that the knee in their spectrum is formed by a component of cosmic rays of a non-nuclear nature, possibly consisting of stable (quasi-stable) particles of hypothetical strange quark matter, which named strangelets. This is the only model of the knee compatible with the magnetic rigidity of the nuclear spectra break R=100 TV. In fact, stranglets are stable heavy quasi-nuclei with a positive electric charge of Z=30-1000, so the mechanism of their acceleration coincides with the nuclear one. The break of the cosmic ray spectrum can be associated with a significantly larger mass of strangelets compared to nuclei.